(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Knee osteoarthritis (OA) is a degenerative joint disease with increasing global prevalence, especially among the elderly population. This condition causes persistent pain, joint stiffness, and significant decline in physical function. This study aimed to evaluate the effectiveness of socialization about the benefits of ultrasound therapy and quadriceps strengthening exercises in improving knee OA patients’ understanding of their condition management. The socialization activity was conducted in December 2025 at Puskesmas X Lubuk Pakam, involving 18 elderly knee OA patients. The methods used included initial understanding measurement using a questionnaire, interactive material delivery about ultrasound mechanisms and quadriceps exercises, and final understanding measurement after socialization. The questionnaire consisted of 20 questions covering knowledge about knee OA, ultrasound benefits, and quadriceps exercise principles. Results showed a significant improvement in participants’ understanding, with average pre-socialization score of 8.4 (SD 2.1) increasing to 16.7 (SD 1.8) post-socialization (p<0.001). Sixteen participants (88.9%) experienced understanding improvement above 70%, and 17 participants (94.4%) expressed satisfaction with the delivered material. Data analysis showed a positive correlation between increased understanding and participants’ interest in applying independent exercises (r=0.82; p<0.001). It was concluded that socialization about the benefits of ultrasound and quadriceps exercises effectively improved knee OA patients’ understanding, making it worthy of continuous implementation in primary healthcare facilities.